The Impact of Macroeconomic Variables on the Performance of the SRI-KEHATI Index on the Indonesia Stock Exchange (2017–2024) - Muhammad Ulul Albab (Jurnal Ilmiah Manajemen dan Bisnis, 2026)
This study investigates the impact of selected macroeconomic indicators on the performance of the SRI-KEHATI Index in Indonesia during the 2017–2024 period. The explanatory variables consist of inflation, the policy interest rate, the rupiah to US dollar exchange rate, and gross domestic product (GDP), while the dependent variable is the SRI-KEHATI Index return. Employing a quantitative approach, the research applies a time series regression framework, preceded by stationarity diagnostics and supported by classical assumption tests to ensure statistical validity. Data were obtained from authoritative sources including Bank Indonesia, Statistics Indonesia, and the Indonesia Stock Exchange. The empirical results indicate that the exchange rate has a significant negative effect on the index performance, suggesting that rupiah depreciation tends to weaken sustainable stock returns. Conversely, inflation, interest rates, and GDP are found to have no statistically significant impact on the index within the observed period. These findings highlight the strategic importance of exchange rate stability in shaping sustainability-oriented investment strategies and provide valuable insights for policymakers, investors, and corporations seeking to strengthen their commitment to environmental, social, and governance (ESG) principles in the Indonesian capital market.